A computer method for moment-curvature analysis of composite steel-concrete cross-sections of arbitrary shape. Issue 1 (2nd January 2017) - Chiorean, Cosmin G.
Abstract: This paper presents a new computer method for moment-curvature analysis of arbitrary-shaped composite steel-concrete cross-sections that are subjected to biaxial bending and axial force. The complete moment-curvature diagrams are determined such that axial force and bending moment ratio is kept constant. A strain-driven algorithm has been developed, the solution of the nonlinear equilibrium equations is controlled by the assumed strain values in the most compressed point and by solving just two coupled nonlinear equations. Such an approach may be used to assess accurately the main features of the elasto-plastic behaviour of composite cross-sections: multiple yielding points associated to different materials, flexural and axial rigidity, moment-curvature relationship in pre and post-critical domain and curvature ductility detecting also unloaded regions of the cross-sections that may occur even under monotonically increasing of the total bending moment. Since the Jacobian's of the resulted nonlinear system of equations is always positive definite the convergence stability is not sensitive to the initial/starting values of the iterative process and to the strain softening exhibited by the concrete in compression. By using a path integral technique on boundary of cross-section area, gradual spread of plasticity and residual stress distribution assumed for encased steel elements are accurately considered reducing also the computational time significantly. In order to illustrate the proposed method and its accuracy and efficiency, a computer program has been developed and used to study several representative examples. The numerical studies presented and comparisons made prove the effectiveness and time saving of the proposed method of analysis.